The Role of Women Entrepreneurs in Advancing Gender Equality and Social Change - Giriraj Kiradoo (Research Aspects in Arts and Social Studies Vol. 8, 2023)
This research explores women entrepreneurs’ critical role in advancing gender equality and driving social change. By adopting a multifaceted approach, this study delves into the complex interplay between women’s entrepreneurship, gender norms, and social structures. This investigation uses a mixed-methods research design to uncover the factors that enable and inhibit women entrepreneurs’ agency in promoting gender equality and social change. This research is stranded in the theoretical framework of feminist entrepreneurship, which recognises women’s unique challenges and opportunities in starting and running their own businesses. Through an intersectional lens, this study examines how social identities, including race, class, and sexuality, interact with gender in shaping women entrepreneurs’ experiences. Drawing on qualitative interviews with women entrepreneurs, as well as surveys and secondary data analysis, this study seeks to identify the strategies that women entrepreneurs use to challenge gender norms and promote social change. This research investigates the impact of women-owned businesses on local economies, communities, and social structures. The findings of this study have substantial implications for policymakers, practitioners, and scholars interested in promoting gender equality and social change through entrepreneurship. By illuminating the critical role of women entrepreneurs in driving social change, this research can inform the design of policies and programs that support and enable women’s entrepreneurship. Ultimately, this study seeks to contribute to a more comprehensive understanding of how women entrepreneurs can advance gender equality and promote social change.